Attendance Monitoring Application for Students using RFID - Abdul Hanis, Hazirah Izzati; Ramli, Sofia Najwa (Applied Information Technology And Computer Science, 2021)
Coronavirus Disease 2019 (COVID-19) is affecting different age groups including school students. The safety of those students needs to be put as a priority by our government when they attend the school for teaching and learning. However, Sekolah Menengah Kebangsaan Tun Habab is still gathering the attendance information using attendance book at the school entrance that may be a potential for spreading COVID19. Therefore, this project focuses on designing an application that helps the school to record student attendance data using RFID. The chosen methodology to develop the application is SDLC Waterfall Model. The application is developed using Arduino. The proposed application records the student’s RFID ID, time, and date every time they check-in to the school via the application. In conclusion, the project may lessen the problem that has been facing by the school and the students such as using manual way to record the student’s information before entering school that may put them on risk of spreading the virus of Coronavirus Disease 2019 (COVID-19) as they are using the same equipment to write down their information, the potential of losing the data due to natural disaster, and some of the students cannot afford to buy smartphones to use the existing application.